FACTORS INFLUENCING WORD OF MOUTH INTENTION IN THE HEALTHY RESTAURANT INDUSTRY IN JAKARTA, INDONESIA - bernarto, innocentius (Archives of Business Research, 2020)
This research aims to understand whether food quality, personal interaction quality, physical environment qualtiy, and perceived value are positively related to satisfaction and its impact to commitment, trust, and word of mouth. The target population are customers who dined in healthy restaurants in Jakarta. The data was collected using questionnaire. There was a total of 403 respondents involved using convenience sampling method. The data was analyzed using Partial Least Square-Structural Equation Modeling approach of SmartPLS 3.0 software. The results show that the food quality, personal interaction quality, physical environment quality, and perceived value were positively related to satisfaction. In addition, satisfction was also positively related to trust, commitment, and word of mouth. Meanwhile, commitment was positively related to word of mouth. However, trust was not positively related to word of mouth. Keywords: Food Quality, Personal Interaction Quality, Physical Environment Quality, Perceived Value, Satisfaction, Trust, Commitment, Word of Mouth.